A novel copper(ii)–lanthanum(iii) metal organic framework as a selective catalyst for the aerobic oxidation of benzylic hydrocarbons and cycloalkenes. Issue 11 (27th January 2016) - Cancino, P.; Vega, A.; Santiago-Portillo, Andrea; Navalon, Sergio; Alvaro, Mercedes; Aguirre, P.; Spodine, E.; García, Hermenegildo
Abstract : The synthesis and catalytic activity of a novel heteronuclear Cu II and La III metal organic framework (MOF) having pyridinedicarboxylic acid (CuLa-MOF) is reported. Abstract : The synthesis and structure of a novel heteronuclear Cu II and La III metal organic framework (MOF) having pyridinedicarboxylic acid (CuLa-MOF) is reported. The obtained MOF with the formula [Cu0.5 La2 (HPDC)(PDC)2 (SO4 )(H2 O)2 ]H2 O n (PDC: 3, 5-pyridinedicarboxylate) has a 3D non-porous lattice with a single type of octahedrally coordinated Cu II and two distinct nonacoordinated La III ions, with sulphate being a linker between the Cu II and La III centers. CuLa-MOF exhibits catalytic activity to promote the aerobic autooxidation of benzylic hydrocarbons and the aerobic oxidation of cycloalkenes. Compared with a homogenous catalyst, Cu(OAc)2, CuLa-MOF, as a heterogeneous catalyst, exhibits similar activity, but the solid is recyclable with some minor decrease in activity from the first to the second catalytic cycle; after which, a steady activity is observed, as determined by the coincidence of temporal evolution of the reaction upon reuse.